2006
DOI: 10.1590/s0102-311x2006001200021
|View full text |Cite
|
Sign up to set email alerts
|

Os riscos dos acidentes de trânsito na perspectiva dos moto-boys: subsídios para a promoção da saúde

Abstract: Esta nota resulta de uma pesquisa qualitativa realizada na cidade de Porto Alegre, Rio Grande do Sul, Brasil, com o objetivo de explorar o fenômeno "risco do acidente de trânsito" na perspectiva de moto-boys. O estudo foi embasado nas teorias sociológicas sobre risco, em especial, as que enfatizam o caráter sócio-cultural dos seus significados. As informações foram coletadas por meio de grupos focais e analisadas seguindo os passos da Teoria Fundamentada nos Dados. Segundo os moto-boys, os riscos do acidente d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
29

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 1 publication
1
24
0
29
Order By: Relevance
“…6 As for motorcycle accidents, a similar trend to that of other Brazilian cities is seen Vitória where most victims are young adults. 22 In regard to suicides, corroborating the fi ndings of the present study 7 , other studies showed higher rates among adults aged 35-54.…”
Section: Discussionsupporting
confidence: 91%
“…6 As for motorcycle accidents, a similar trend to that of other Brazilian cities is seen Vitória where most victims are young adults. 22 In regard to suicides, corroborating the fi ndings of the present study 7 , other studies showed higher rates among adults aged 35-54.…”
Section: Discussionsupporting
confidence: 91%
“…Urgency is "as important in the work of a motoboy as to guarantee their job". 17 A qualitative study in the city of Campinas, in the state of São Paulo, while discussing the relationship between motorcyclists and traffi c violations, pointed out that the motorcycle was viewed by them as a symbol of adventure and challenge. 5 Among several intervention strategies to reduce these injuries are: the creation of motorcycle-only lanes on high-risk roads; qualifi cation courses for motoboys, given by more experienced motorcyclists; 13 use of bright-colored clothing and accessories; promotion of traffi c rules of sociability; 13 and the involvement of employers and service clients with safety issues.…”
Section: Discussionmentioning
confidence: 99%
“…2,9,11,59 In four large urban centers ( 32,64 The motorcycle as a means of work is regarded as a potential factor for increased motorcycle casualties, 2,9,11,59 and motorcycle couriers are at high risk of RTA due to their job demands. 19,36,64,73 In São Paulo k and Porto Alegre 74 37% of deaths and 28% of emergency hospital admissions of motorcyclists were among motorcycle couriers. Pressure from customers and employers for fast deliveries, 19,73 pay on the basis of productivity and daily work shifts exceeding 10 hours 19,64 have been identifi ed as determinants of inappropriate driving.…”
Section: Motorcyclesmentioning
confidence: 99%